2011
DOI: 10.1029/2010jb007768
|View full text |Cite
|
Sign up to set email alerts
|

Building of the Amsterdam-Saint Paul plateau: A 10 Myr history of a ridge-hot spot interaction and variations in the strength of the hot spot source

Abstract: [1] The Amsterdam-Saint Paul plateau results from a 10 Myr interaction between the South East Indian Ridge and the Amsterdam-Saint Paul hot spot. During this period of time, the structure of the plateau changed as a consequence of changes in both the ridge-hot spot relative distance and in the strength of the hot spot source. The joint analysis of gravity-derived crust thickness and bathymetry reveals that the plateau started to form at ∼10 Ma by an increase of the crustal production at the ridge axis, due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 74 publications
2
41
0
Order By: Relevance
“…Considering those samples as representative of the bulk composition of the seamounts, we can explain this observation as follows: (1) the large old seamounts may result from larger degrees of melting, and therefore exhibit a more dilute enriched signature because of mixing with local depleted mantle melts and (2) the youngest seamounts, which formed above lithospheric cracks [ Janin et al , 2011], would result from lower degrees of melting of more enriched materiel left by the plume under or in the lithosphere. Maia et al [2011] suggested an episodic activity of ASP mantle plume. In the frame of Maia et al models, the youngest seamounts are related to the second pulse which constructed the ASP plateau [ Janin et al , 2011].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering those samples as representative of the bulk composition of the seamounts, we can explain this observation as follows: (1) the large old seamounts may result from larger degrees of melting, and therefore exhibit a more dilute enriched signature because of mixing with local depleted mantle melts and (2) the youngest seamounts, which formed above lithospheric cracks [ Janin et al , 2011], would result from lower degrees of melting of more enriched materiel left by the plume under or in the lithosphere. Maia et al [2011] suggested an episodic activity of ASP mantle plume. In the frame of Maia et al models, the youngest seamounts are related to the second pulse which constructed the ASP plateau [ Janin et al , 2011].…”
Section: Discussionmentioning
confidence: 99%
“…The construction of the ASP plateau began about 10 Myr ago [ Maia et al , 2008, 2011] and resulted in two separate magmatic stages: on‐axis and off‐axis successively. The difference between on‐ and off‐axis magmatism is highlighted by the morphology of the structure with (1) on‐axis magmatism, building a thicker oceanic crust, and (2) off‐axis magmatism, occurring later, and resulting into the construction of seamounts on the oceanic floor.…”
Section: Geological Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ASP Plateau is presently in a period of diminishing plume‐ridge interaction indicated by a decrease in axial crustal thickness since 1.4 Ma. Using high‐resolution bathymetric (gridded at 200 m) and gravity data (gridded at 1 km) as well as magnetic anomalies from the PLURIEL (September/October 2006) and BOOMERANG 06 expeditions (February/April 1996; Maia et al, ; Scheirer et al, ), we present a detailed analysis of the Amsterdam‐St. Paul Plateau and of the morphological evolution of the SEIR axis during the last 3 Myr.…”
Section: Introductionmentioning
confidence: 99%
“…(a) Bathymetric map of the Amsterdam‐St. Paul Plateau based on multibeam data from Maia et al () and the regional map with depth anomaly (inset). The ASP plume has been approaching (black circles show approximate locations since 9 Ma) the SEIR (thin, black lines) for >10 Ma.…”
Section: Introductionmentioning
confidence: 99%